2008
DOI: 10.1186/1471-2407-8-345
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity, age, race and stage at diagnosis in colorectal cancer: a retrospective, parallel analysis of two health systems

Abstract: Background: Stage at diagnosis plays a significant role in colorectal cancer (CRC) survival. Understanding which factors contribute to a more advanced stage at diagnosis is vital to improving overall survival. Comorbidity, race, and age are known to impact receipt of cancer therapy and survival, but the relationship of these factors to stage at diagnosis of CRC is less clear. The objective of this study is to investigate how comorbidity, race and age influence stage of CRC diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 51 publications
2
28
3
Order By: Relevance
“…Veteran patients with colorectal cancer tend to have multiple comorbidities and are significantly older than the average nonveteran patient population [19][20][21]. Therefore, we hypothesized that our colorectal cancer veteran patient population was ideally suited to evaluate the potential benefits of MIS in short-term outcomes in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Veteran patients with colorectal cancer tend to have multiple comorbidities and are significantly older than the average nonveteran patient population [19][20][21]. Therefore, we hypothesized that our colorectal cancer veteran patient population was ideally suited to evaluate the potential benefits of MIS in short-term outcomes in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Within the 13 identified studies, nine studies reported on the effect of comorbidity on stage at diagnosis [9][10][11][12][13][14][15][16][17], and five studies reported on healthcare utilization prior to diagnosis and its effect on stage at diagnosis [13,[18][19][20][21]. Full details of study selection, including reasons for exclusion of studies, can be seen below in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When comorbidity was determined using a summary measure, the presence of comorbidity was associated with a later stage of CRC diagnosis in one study [11] and had no effect on CRC stage at diagnosis in two studies [10,15] as well as no effect in identified subgroups in two studies: the male cohort in one [12] and a cohort of fee-for-service patients in the other (compared to a cohort from the Veterans Health Administration) [17]. Comorbidity was associated with an earlier stage of CRC at diagnosis in one study [13], and the subgroups in two studies: the female cohort in one study [12] and a cohort of patients from the Veteran's Health Administration [17].…”
Section: Comorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of developing colorectal carcinoma increases with age [3] . It has been seen that about 90% of new cases are diagnosed in patients over 50 years of age [4] . The literature suggests that there is a gradual shift of colon cancer towards right [5] .…”
Section: Introductionmentioning
confidence: 99%